Understanding event-generation networks via uncertainties - Bellagente, Marco; Haußmann, Manuel; Luchmann, Michel; Plehn, Tilman (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 13, 003 (2022) Understanding Event-Generation Networks via Uncertainties
Gesehen am 17.08.2022